Intervening in the Lives of Gang Members in Denver: A Pilot Evaluation of the Gang Reduction Initiative of Denver. (3rd July 2019) - Pyrooz, David; Weltman, Elizabeth; Sanchez, Jose
Abstract: There are over one million gang members in the United States, but effective practices and programs to facilitate disengagement from gangs are rare. This first aim of this article was to introduce the intervention strategy of the Gang Reduction Initiative of Denver (GRID), a public agency operating at the core of a network of partners seeking to reduce gang violence in Denver. GRID uses a multidisciplinary team approach with coordinated and individualized case management and street outreach workers to facilitate disengagement from gangs and desistance from crime. The second aim of this article was to report the results of a pilot project evaluation, which entailed baseline interviews with 57 clients and follow-up interviews with 20 clients. Reductions in gang status, gang embeddedness, and offending were observed, as well as positive client–outreach relationships. The final aim was to report the steps toward establishing a foundation to conduct a full-scale evaluation. Most responses to gangs are considered promising because they have not been subject to rigorous evaluation. GRID aims to stand in contrast to most of the current inventory of justice evaluations of gang interventions through a process and impact evaluation consisting of random assignment to treatment and control groups.